Strategi Penerjemahan Unsur Linguistik dalam Audio Description Film Horor Indonesia: Studi Kasus Pengabdi Setan (2017) - Widrayani Widrayani; Nurfithri Nurfithri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores translation strategies of linguistic elements in the Audio Description (AD) of the Indonesian horror film Pengabdi Setan (2017), focusing on how translators mediate audio-visual information for visually impaired audiences. Employing a qualitative, descriptive-analytical approach within an embedded single-case study design, the research analyzes film scenes containing significant linguistic cues alongside their official AD scripts. The study identifies five main translation techniques based on Molina and Albir (2002): substitution, reduction, description, amplification, and modulation, which are often combined to achieve coherent, emotionally resonant narration. Substitution transforms sounds into textual equivalents, amplification expands implicit meanings, reduction condenses non-essential information, and modulation shifts perspectives to maintain narrative tension. Data analysis demonstrates that these strategies effectively convey horror elements, suspense, and character emotions while respecting the original sound design. Findings highlight the translator’s role as an active mediator, balancing accessibility with aesthetic and psychological effects. The study contributes to understanding the complexity of AD in horror films and underscores its interpretative, creative, and strategic dimensions in enhancing audience experience.